Effects of an AT1 receptor antagonist, an ACE inhibitor and a calcium channel antagonist on cardiac gene expressions in hypertensive rats. - Kim, S. (1996)
1. This study was undertaken to determine whether the AT1 receptor directly contributes to hypertension-induced cardiac hypertrophy and gene expressions. 2. Stroke-prone spontaneously hypertensive rats (SHRSP) were given orally an AT1, receptor antagonist (losartan, 30 mg kg-1 day-1), an angiotensin converting enzyme inhibitor (enalapril 10 mg kg-1 day-1), a dihydropyridine calcium channel antagonist (amlodipine, 5 mg kg-1 day-1), or vehicle (control), for 8 weeks (from 16 to 24 weeks of age). The effects of each drug were compared on ventricular weight and mRNA levels for myocardial phenotype- and fibrosis-related genes. 3. Left ventricular hypertrophy of SHRSP was accompanied by the increase in mRNA levels for two foetal phenotypes of contractile proteins (skeletal alpha-actin and beta-myosin heavy chain (beta-MHC)), atrial natriuretic polypeptide (ANP), transforming growth factor-beta-1 (TGF-beta 1) and collagen, and a decrease in mRNA levels for an adult phenotype of contractile protein (alpha-MHC). Thus, the left ventricle of SHRSP was characterized by myocardial transition from an adult to a foetal phenotype and interstitial fibrosis at the molecular level. 4. Although losartan, enalapril and amlodipine lowered blood pressure of SHRSP to a comparable degree throughout the treatment, losartan caused regression of left ventricular hypertrophy of SHRSP to a greater extent than amlodipine (P < 0.01). 5. Losartan significantly decreased mRNA levels for skeletal alpha-actin, ANP, TGF-beta 1 and collagen types I, III and IV and increased alpha-MHC mRNA in the left ventricle of SHRSP. Amlodipine did not alter left ventricular ANP, alpha-MHC and collagen types I and IV mRNA levels of SHRSP. 6. The effects of enalapril on left ventricular hypertrophy and gene expressions of SHRSP were similar to those of losartan, except for the lack of inhibition of collagen type I expression by enalapril. 7. Unlike the hypertrophied left ventricle, there was no significant difference between losartan and amlodipine in the effects on non-hypertrophied right ventricular gene expressions of SHRSP. 8. Our results show that hypertension causes not only left ventricular hypertrophy but also molecular transition of myocardium to a foetal phenotype and interstitial fibrosis-related molecular changes. These hypertension-induced left ventricular molecular changes may be at least in part mediated by the direct action of local angiotensin II via the AT1, receptor.